Three new species of bacterivorous Chrysopetalidae and Microphthalmidae (Annelida) inhabiting a whale fall off eastern Australia. - Charlotte Watson; Laetitia M. Gunton; Elena K. Kupriyanova (Records of the Australian Museum)
A natural whale fall was opportunistically trawled at ~1000 m depth during the 2017 research vessel ‘Investigator’ voyage whilst sampling bathyal and abyssal communities along the eastern Australian margin. Colonising the whale bones were a diverse assemblage of annelids including three new species of free-living Phyllodocida (Boudemos paulinae sp. nov, Pleijelius keni sp. nov. and Microphthalmus hvalr sp. nov.). Boudemos paulinae sp. nov. (Chrysopetalidae, Calamyzinae) is a smaller sized species (< 2 mm) compared to its congeners (35-40 mm) and exhibits stylet jaw and notochaetal morphology observed in juveniles of the sister species Boudemos flokati (Dahlgren, Glover, Baco & Smith, 2004) from whale falls in the NE Pacific. Notochaetal serration patterns distinguish Pleijelius keni sp. nov. from its only congener P. longae Salazar-Vallejo & Orensanz, 2006 described in the family Hesionidae from wood falls in NW Atlantic. DNA sequence analysis using the COI, 16S and 18S gene fragments revealed Pleijelius keni sp. nov. fell within the Microphthalmidae clade, this relationship was also supported by morphological observations. These results necessitated a formal transfer of the genus Pleijelius to the family Microphthalmidae. Microphthalmus hvalr sp. nov. is the first Microphthalmus species described from bathyal depths and is distinguished from its numerous congeners inhabiting shallow-water interstitial sediments by the absence of notochaetae.